How do you solve \frac { - 3} { x + 7} = \frac { 8} { x - 4}?

2 Answers

x=4

Explanation:

-3(x-4)=8(x-7)
-3x+12=8x+56
12-56=8x+3x
-44=11x
x=-44/11
x=-44/11

here x can never be 0 or -7 as these can make denominators zero

Nov 6, 2016

x=-4

Explanation:

(-3)/(x+7)=8/(x-4)

Cross multiply.

-3(x-4)=8(x+7)

Expand both sides.

-3x+12=8x+56

Add 3x to both sides.

12=8x+56+3x

12=11x+56

Subtract 56 from both sides.

12-56=11x

-44=11x

Divide both sides by 11.

-44/11=x

-4=x

Switch sides.

x=-4